Improvement in fatigue and sleep measures with the dual orexin receptor antagonist lemborexant in adults with insomnia disorder. Issue 3 (3rd April 2022) - Chepke, Craig; Jain, Rakesh; Rosenberg, Russell; Moline, Margaret; Yardley, Jane; Pinner, Kate; Kumar, Dinesh; Perdomo, Carlos; Filippov, Gleb; Atkins, Norman; Malhotra, Manoj
ABSTRACT: Objective: Fatigue is a common symptom in patients with insomnia. This analysis evaluated whether treatment of nighttime symptoms of insomnia with a dual orexin receptor antagonist, lemborexant, might also reduce fatigue. Methods: Analyses were conducted of two phase 3 studies of subjects with insomnia disorder. Subjects received placebo, lemborexant 5 mg, or lemborexant 10 mg in the 12-month (6 months placebo-controlled) Study E2006-G000-303 (Study 303: SUNRISE-2) of adults (N = 949; full analysis set [FAS]), and the 1-month, placebo- and active-controlled Study E2006-G000-304 (Study 304; SUNRISE-1) of older adults (females ≥55 years, males ≥65 years) (N = 1006; FAS). Fatigue was assessed using the Fatigue Severity Scale (FSS). Patient-reported sleep onset and maintenance endpoints were analyzed using data from electronic sleep diaries. Results: Lemborexant significantly reduced subject-reported fatigue versus placebo over a 6-month treatment period (FSS total score least-squares mean treatment difference of −2.50 for 5 mg and −2.56 for 10 mg of lemborexant; p < 0.05 for both). This reduction was sustained over 12 months of lemborexant in both the overall population and in subjects with clinically meaningful fatigue (FSS total score ≥36) at baseline. Improvements in fatigue over time positively correlated with improvements in sleep onset and maintenance parameters. Improvements in sleep quality were evident as early as 1 week after lemborexant treatment, whereas longer-term treatment (>1 month) may be needed for improvements in insomnia-related fatigue. Conclusions: In addition to improving sleep onset and sleep maintenance in subjects with insomnia disorder, lemborexant provides further benefit by reducing daytime fatigue. Clinical trial registration: https://clinicaltrials.gov/ct2/show/NCT02952820 and https://clinicaltrials.gov/ct2/show/NCT02783729 Abbreviations: DSM-5 = Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition ; FSS = Fatigue Severity Scale; ICSD-3 = International Classification of Sleep Disorders, Third Edition ; LSM = least squares mean; sSE = subjective sleep efficiency; sSOL = subjective sleep onset latency; sTST = subjective total sleep time; sWASO = subjective sleep after wake onset.